Evaluation of effective factors of hearing protection use in tile workers - Z Loukzadeh; AH Mehrparvar; A Shojaaddini Ardekani; R Nabi Meybodi (طب کار)
Abstract Background: Noise-induced hearing loss is among the most common occupational diseases and is completely preventable despite being permanent and irreversible. Although management and engineering control are in prior, for some reasons its implementation is difficult in certain circumstances. So, Hearing Protection Devices (HPDs) are often the only method. But most of workers exposed to high level noise do not use them. The aim of this study was to detect factors influencing on usage of HPDs by workers based on Pender’s Health Promotion Model and safety climate. Methods: In this study, 121 tile workers who exposed to sounds ≥ 85dB were evaluated. A questionnaire including demographic date, HPDs using frequency, worker’s self-efficacy regarding HPDs use as well as workers’ perceptions of management’s commitment to HPDs use and safety was completed for them. Results: Our research showed that 24% of workers used HPDs for more than 50% of work duration. Only 10% of the workers used it for more than 90% of work duration. There was a significant difference in scores related to “Safety climate” and also one of the items of “HPDs usage barriers” between the group who used HPDs>50% of work duration and the group≤50% (p=0.04 and p=0.06 respectively). Conclusion: Despite exposure to noise and being subject to noise-induced hearing loss, prevalence of HPDs use is low. In this survey, the belief that wearing HPDs is not uncomfortable and safety climate were important factors for HPDs usage. Therefore, manager support for working in safety climate including HPDs use, education of using method and its importance in preventing hearing loss have significant influences on increasing HPDs use